A Built-In Mixed-signal Block Observer (BIMBO) to improve observability in 1149.4 environments - Felgueiras, Manuel C. (2017)
This document proposes an extension to the IEEE 1149.4 test infrastructure [1], whereby a bank of sigma-delta first order modulators enables the simultaneous observation of several analog pins in a single component. The modulator output bit streams are shifted out and made available to an external test controller that comprises the corresponding bank of decimation filters and other decision and control logic. The architecture proposed is fully non-intrusive and may be used to support debug and test operations in mixed-signal environments.